Association of family wellbeing with forwarding and verifying COVID-19-related information, and mediation of family communication quality - Wong, Bonny Yee-Man; Ho, Sai Yin; Sit, Shirley Man Man; Gong, Wei Jie; Lai, Agnes Yuen Kwan; Wang, Man Ping; Lam, Tai Hing (Frontiers in Public Health, 2022)
Objective: We assessed the associations of family well-being with verifying and subsequently forwarding COVID-19-related information to family members and the mediating effect of the quality of family communication on these associations among Chinese adults in Hong Kong. Methods: Under the Jockey Club SMART Family-Link Project, we conducted an online population-based survey, using Family Well-being Scale and questions related to family communication quality and forwarding and verifying COVID-19 information. Data were collected from 4891 adults in May 2020. Prevalence estimates of forwarding and verifying COVID-19 information were weighted by sex, age, and education of the general population, and their associations with family well-being (ranged 0-10) were analysed using generalised linear models with mutual adjustment. Their interactive effects on family well-being and the mediating effects of family communication quality were examined. Results: 53.9% of respondents usually/always forwarded COVID-19 information-related to their family, 68.7% usually/always verified it before forwarding, and 40.9% did both. Greater family well-being was associated with usually/always forwarding (adjusted β [95% CI]: 0.82 [0.72-0.92]) and usually/always verifying (0.43 [0.32-0.55]) (both P<0.001) the information. Forwarding and verifying such information showed an additive effect on family well-being (1.25 [1.11-1.40]). Family communication quality mediated the associations of family well-being with forwarding (83.7%) and verifying (86.6%) COVID-19-related information. Conclusion: Forwarding COVID-19 information to family, verifying such information, and especially doing both, were associated with greater family well-being, being strongly mediated by the quality of family communication. Individuals should be encouraged to verify COVID-19-related information before forwarding to family members amidst the COVID-19 pandemic.